Iron requirements and uptake strategies of the globally abundant marine ammonia-oxidising archaeon, Nitrosopumilus maritimus SCM1 - Shafiee, R; Snow, J; Zhang, Q; Rickaby, R (Springer Nature, 2019)
Ammonia-oxidising archaea (AOA) mediate the rate-limiting step of nitrification, the central component of the marine nitrogen cycle that converts ammonia to nitrite then nitrate. Competition with phytoplankton for ammonium and light inhibition are considered to restrict AOA activity to below the photic zone, but observations of surface nitrification now demand a further understanding of the factors driving AOA distribution and activity. Pico- to nanomolar concentrations of iron (Fe) limit the growth of microorganisms in a significant portion of the world's surface oceans, yet there is no examination of the role of Fe in AOA growth despite the process of ammonia oxidation being considered to rely on the micronutrient. Here we investigate the Fe requirements and Fe uptake strategies of the Nitrosopumilus maritimus strain SCM1, a strain representative of globally abundant marine AOA. Using trace metal clean culturing techniques, we found that N. maritimus growth is determined by Fe availability, displaying a free inorganic Fe (Fe') half saturation constant 1-2 orders of magnitude greater for cell growth than numerous marine phytoplankton and heterotrophic bacterial species driven by a reduced affinity for Fe'. In addition, we discovered that whilst unable to produce siderophores to enhance access to Fe, N. maritimus is able to use the exogenous siderophore desferrioxamine B (DFB), likely through a reductive uptake pathway analogous to that demonstrated in phytoplankton. Our work suggests AOA growth in surface waters may be Fe limited and advances our understanding of AOA physiology on the cellular and mechanistic levels with implications for ecosystem dynamics and the biogeochemical N-cycle.